Promoting a strong seed sector in Sub-Saharan Africa - Minot, Nicholas (International Food Policy Research Institute, 2008)
Given that Sub-Saharan Africa has the highest incidence of poverty and malnutrition in the world, the stagnation in per capita grain production there is worrisome. Since 1970, per capita grain production in Sub-Saharan Africa has declined more than 10 percent. Increasing the productivity of staple foodcrops will help poor farmers and consumers, and one of the most sustainable ways to expand food production in Sub-Saharan Africa is to generate new technologies-including staple seed varieties-that are adapted to the constraints of the continent's small-scale farmers. The region thus requires a cost-effective system of seed production and distribution to ensure that appropriate seeds are delivered to farmers.Both the private and public sectors have a role to play in developing the seed sector in Sub-Saharan Africa. Although the private sector can effectively carry out many seed production and distribution activities, for reasons discussed in this brief, private companies acting on their own will not develop and produce optimal amounts of appropriate seeds for Sub-Saharan Africa. Thus the public sector also has a role to play.